ANALISIS PENGARUH PELAPISAN NIKEL PADA MATERIAL ALUMINIUM SERI 2024 TERHADAP KEKUATAN TARIK DAN KEKERASAN DENGAN METODE ELEKTROPLATING - Fatir Slametriadi Fatir; Sehono; Ferry Setiawan (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
Aluminum alloy in the aerospace field has been widely used in the manufacture of skins from aircraft. The use of aluminum alloy has the advantages of relatively high mechanical strength and resistance to corrosion. In order to raise the strength of the material and the physical appearance of aluminum can use the electroplating method. Electroplating is a method used to coat metals with other types of metals, the coating process uses the help of electric current. The electric current used will trigger the release of metal ions at the anode to be further attached to the cathode. In this study, an electroplating process was carried out on 2024 aluminum alloy specimens with nickel coating. The variations in this study used differences in electric current voltages of 25 V, 35 V, and 45 V. Then to find out the differences from the variations that have been used, tensile tests and hardness tests were carried out. From the results of the tensile test, it shows that the higher the voltage of the electric current used, it will increase the tensile strength, but the yield strength will decrease. The highest tensile strength is found in the voltage variation of 45 V with a value of 452.53 MPa. Then on the hardness test shows that the higher the voltage of the electric current will reduce the hardness value. The highest hardness value is found at a voltage of 25 V with a value of 963.594.